Makna Simbol “ZERO” Sebagai Pesan Non Verbal Yayasan Matahati Dalam Mencegah Penyebaran HIV Aids Di Kawasan Pangandaran - Ditha Prasanti; Hadi Suprapto Arifin; Ikhsan Fuady (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
This article is the result of a study of health communication studies on HIV AIDS prevention and prevention by the Matahati Foundation in Pangandaran district. Like the iceberg phenomenon, the number of HIV AIDS in Pangandaran district is increasing, so that it attracts the attention of various parties, one of which is the Matahati Foundation. In this article, the method which used is qualitaitv method, in line with the aim of research that is describes the existence of a symbol used by the Matahati Foundation, namely the symbol